Oxford Handbook of Respiratory Medicine, 1st Edition - Chapman, Stephen, Robinson, Grace; Stradling, John; West, Sophie (OXFORD UNIVERSITY PRESS, 2005)
This Handbook of Respiratory Medicine has been written largely by specialist registrars, for specialist registrars. Three of the four authors, Stephen Chapman, Grace Robinson, and Sophie West, are specialist registrars on the Oxford rotation and John Stradling is Professor of Respiratory Medicine in Oxford. It is in a format that the authors would like to have had when they started their specialist registrar training. However, we hope that any health worker or student with an interest in respiratory medicine will find this text a rapid and useful reference source. The layout of the book tries to fulfil the requirement to be able to look up a topic quickly when the clinical need arises, but also to provide a bit more insight into the more difficult areas. Therefore the chapters are of necessity different in style and reflect the authors' own views on how to best approach and understand an area. The handbook is divided into five sections: clinical presentations and approaches to symptoms and problems; the clinical conditions themselves; supportive information; procedures; and useful appendices (also on the inside covers), containing more technical and reference information.